Strategic governance : a division of labour in New Zealand companies : a ... thesis presented in partial fulfilment of the requirements of the degree of Master of Business Studies at Massey University - Ellett, Maurice Charles (Massey University, 2003)
Much of the research in the disciplines of strategic management and governance has taken place in the United States where the Chairman of the board is frequently carrying the position of Chief Executive Officer. To date, New Zealand studies into these disciplines have largely been anecdotal. This research examines the strategic management and governance processes adopted by the executive management and board in twelve large New Zealand companies. Although some of the data categories were structured prior to analysis by the questions, a grounded theory approach (Locke, 1996) is adopted for the synthesis and evaluation of the data. Semi-structured interviews were conducted with both the CEO and Chair of nine of these companies. Questions focused on board composition, governance processes and roles in developing and executing strategic management. The transcripts were analysed manually and using NUD*IST thematic coding software. Ten concepts were synthesised from the interview transcripts and the questions that created them. The strategic governance processes within these companies satisfied both the Chairs and the CEOs apart from two notable aspects. First, the political agenda of the Government as the shareholder of crown-owned companies impeded the appointment of non-executive directors who could fully deliver to the commercial expectations of the companies. This was compared to companies with and without major shareholders who did not report problems. Conflicts of interest were adjudicated subjectively by the Chair according to the assessed risks involved. Additional services provided commercially to the company by directors were also open to potential conflicts. One characteristic that was evident was the positive working relationships between the Chairs and CEOs of these companies. The research also presents a number of interesting issues, revelations and opinions by these officers.
Keywords: New Zealand; Strategic planning; Corporate governance; Directors of corporations; Chief executive officers